Building A 3D Geological model Using Petrel Software for Asmari Reservoir, South Eastern Iraq - Al-Baldawi, Buraq .A. (Iraqi Journal of Science, 2023)
Building a 3D geological model from field and subsurface data is a typical task ingeological studies involving natural resource evaluation and hazard assessment. Inthis paper a 3D geological model for Asmari Reservoir in Fauqi oil field has beenbuilt using petrel software. Asmari Reservoir belongs to (Oligocene- LowerMiocene), it represents the second reservoir products after Mishrif Reservoir in Fauqifield. Five wells namely FQ6, FQ7, FQ15, FQ20, FQ21 have been selected lying inMissan governorate in order to build Structural and petrophysical (porosity and watersaturation) models represented by a 3D static geological model in three directions.Structural model shows that Fauqi oil field represents un cylindrical anticlinal foldwhich contains number of culminations at northern and southern parts separated bydepressions. After making zones for Asmari reservoir, which is divided into 4 zones(Jeribe/ Euphrates and Kirkuk group which includes Upper Kirkuk, Buzurganmember, Lower and Middle Kirkuk) , Layers are built for each zone of Asmarireservoir depending on petrophysical properties. Petrophysical models (porosity andwater saturation) have been constructed for each zone of Asmari reservoir usingrandom function simulation algorithm. According to data analyses and the resultsfrom modeling, the Upper Kirkuk zone which divided into five layers is a goodreservoir unit regarding its good petrophysical properties (high porosity and low watersaturation) with high presence of oil in economic quantities. Cross sections of porositymodel and water saturation model were built to illustrate the vertical and horizontaldistribution of petrophysical properties between wells of Fauqi oil field.